The Relationship between COVID-19 Vaccination and the Severity of COVID-19 in Patients Treated for the Period August 2021 – August 2022 at Arifin Achmad General Hospital, Riau Province, Indonesia - Ardiansyah, Muhammad Yudhi; Zarfiardy Aksa Fauzi; Rohani Lasmaria S (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The use of the COVID-19 vaccine is very effective in controlling the pandemic, but it is important to know that no vaccine is 100% effective in preventing the COVID-19 pandemic. Vaccination can make the disease milder so that the risk of infection, hospitalization, and death is lower in people who have been vaccinated compared to those who have not been vaccinated. This study aims to determine the relationship between COVID-19 vaccination and the severity of COVID-19 infection in patients treated at Arifin Achmad General Hospital, Riau Province, for the period August 2021 to August 2022. Methods: This study is an analytical observational research with a cross-sectional approach. A total of 403 research subjects were included in this study. Data analysis using Chi-square by looking for the relationship between the dependent variable and the independent variable. Ineligible bivariate data will be performed using the Fisher test with a p-value < 0.05 considered significant based on statistical tests. Results: The percentage of mild and moderate severity patients was generally the highest in the group who did not receive vaccination, with the percentage being 45.8%, followed by those who received booster (30.4%). Of the 54 cases of patients with severe-critical severity, 27 cases were dominated by patients who had no vaccination status at all, with a percentage of 50.0%. Subjects who did not receive vaccination had a 3.37 times higher chance of developing severe COVID-19 than those who were vaccinated (odds ratio = 3,37; 95% confidence interval [THERE] = 1,95-4,80). Conclusion: The relationship between COVID-19 vaccination and the severity of COVID-19 infection in patients treated at Arifin Achmad General Hospital, Riau Province, for the period August 2021 to August 2022.